DISINFORMATION AND DIGITAL ELECTORAL CRIMES: CHALLENGES FOR DEMOCRACY (CIPEEX, 2025)
The spread of disinformation in the digital environment represents one of the greatest challenges to the integrity of the electoral process in contemporary democracies. This paper analyzes the impacts of the dissemination of fake news, especially during electoral periods, and the use of technologies such as artificial intelligence to manipulate public opinion. The research, based on bibliographic and documentary sources, addresses the application of Law No. 9.504/1997 in relation to digital electoral crimes and examines the role of social networks and messaging platforms in the circulation of misleading content. It is observed that technological tools, when used to personalize discourse and micro-target voters, can undermine freedom of choice and equal conditions among candidates.The study also highlights the importance of the actions taken by the Superior Electoral Court (TSE), such as the Program to Combat Disinformation, and advocates for the need for media education as a preventive strategy. Despite institutional progress, challenges remain in regulating digital platforms and holding the authors of manipulative content accountable. It concludes that protecting democracy requires a joint effort between the State, civil society, and technology companies, focusing on effective regulation, algorithmic transparency, and the critical education of voters.The creation of specific legal frameworks and the strengthening of digital citizenship are essential measures to ensure the legitimacy of elections and the preservation of the Democratic Rule of Law.
Keywords: electoral; Artificial Intelligence; Public Policy